2014
DOI: 10.1007/s10549-014-3081-9
|View full text |Cite
|
Sign up to set email alerts
|

Association between germline single nucleotide polymorphisms in the PI3K-AKT-mTOR pathway, obesity, and breast cancer disease-free survival

Abstract: Purpose Obesity-related hormones and cytokines alter PI3K-AKT-mTOR pathway activation in breast tumors contributing to poorer disease-free survival (DFS) and decreased responsiveness to tamoxifen and trastuzumab. We hypothesized that single nucleotide polymorphisms (SNPs) in candidate genes in the PI3K-AKT-mTOR signaling pathway may act as genetic modifiers of breast cancer DFS. Methods We analyzed the association of 106 tagging SNPs in 13 genes (ADIPOQ, IGF1, INS, IRS1, LEP, LEPR, LEPROT, PIK3CA, PIK3R5, PT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…However, an increased risk of BC was not found in two other studies [89,92]. Recently, Pande et al found an association between the IGF-I SNP rs1520220 and poor DFS in women with stage I-II BC [71].…”
Section: Igf-i Snpsmentioning
confidence: 92%
See 3 more Smart Citations
“…However, an increased risk of BC was not found in two other studies [89,92]. Recently, Pande et al found an association between the IGF-I SNP rs1520220 and poor DFS in women with stage I-II BC [71].…”
Section: Igf-i Snpsmentioning
confidence: 92%
“…In a study relating these associations with the clinical evolution, a shorter DFS was related to higher frequency of LEP (22548) A allele, and OS was reduced in patients carrying the LEPR Gln223Arg allele [67]. In contrast, LEPR single nucleotide polymorphism (SNP) rs11585329 (622G.T) has recently been associated with improved DFS in women with stage I-II BC [71].…”
Section: Leptin and Leptin Receptor Single Nucleotide Polymorphismsmentioning
confidence: 99%
See 2 more Smart Citations
“…tumor development and its progression in the case of malignant disease). Some of the established, currently investigated, and potential therapeutic target molecules include: insulin-like growth factor 1 receptor (IGF-1R) [4][5][6][7] ; mechanistic target of rapamycin (mTOR) [8][9][10] ; tyrosine kinases (TKs), such as platelet-derived growth factor receptor (PDGFR) [11,12] and v-kit Hardy-Zuckerman 4 feline sarcoma viral oncogene homolog (KIT) [12] ; epidermal growth factor receptors (EGFRs) [13][14][15] ; vascular endothelial growth factor receptors (VEGFRs) [16] ; poly (ADP ribose) polymerase 1 (PARP-1) [17][18][19] ; phosphatidylinositol 3-kinase (PI3K) [17,20] Aurora A [21] ; human epidermal growth factor receptor 2 (HER2) [22,23] , and Raf/MEK [24] .…”
Section: Introductionmentioning
confidence: 99%